Idiosyncratic risk really drives stock returns; Spanish evidence - Miralles Marcelo, José Luis (2012)
Following the theoretical model of Merton (1987), we provide a new perspective of study about the role of idiosyncratic risk in the asset pricing process. More precisely, we analyze whether the idiosyncratic risk premium depends on the idiosyncratic risk level of an asset as well as the vatriation in the market-wide measure of idiosyncratic risk. As expected, we obtain a net positive risk premium for the Spanish stock market over the period 1987-2007. Our results show a positive relation between returns and individual indiosyncratic risk levels and a negative but lower relation with the aggregate measure of idiosyncratic risk. These findings have important implications for portfolio and risk management and contribute to provide a unified and coherent answer for the main and still unsolved question about the idiosyncratic risk puzzle: whether or not there exists a premium associated to this kind of risk and the sign for this risk premium.